INTEGRACIÓN DE LA PRÁCTICA Y CONOCIMIENTOS DE LA MEDICINA FÍSICA EN LA MEDICINA ACTUAL: La Rehabilitación y Fisioterapia integrativas en la prevención, tratamiento y restauración de la salud. - Ursa Herguedas, Andrés J. (Medicina Naturista)
Physical and Rehabilitation Medicine (PRM) is going through a good moment due to scientific-technical advances, achieving increasingly satisfactory results. Due to world events and their impact on health, the PRM must gradually adopt measures to reduce the economic and environmental impact of health systems. These measures go through promoting the preventive aspect and the incorporation of certain non-conventional medical therapies such as acupuncture, phytotherapy, homeopathy, osteopathy, neural therapy, antihomotoxic therapy, ozone therapy among others, or conventional such as diet therapy, which enjoy scientific evidence and meet safety and efficacy criteria. The objective of this article is to highlight the importance of adopting solutions to make health systems in general and the PRM in particular more sustainable.